Validation of self-assessment instrument for the Patient Safety Center - Renata Soares de Macedo; Elena Bohomol
ABSTRACT Objective: To develop and validate an instrument for the self-assessment of the Patient Safety Centers in health care institutions. Method: Non-experimental methodological study. Divided in the following stages: literature review and construction of the preliminary instrument; content validation by nine professionals with experience in Quality Management and patient safety, who contributed to the adequacy of the items in terms of clarity and relevance; finally, 12 PSC coordinators, which conducted the reliability validation of the final instrument, using Cronbach's Alpha. Results: The instrument presented content validity regarding clarity and relevance, evidenced by an agreement level greater than 70%. The internal consistency presented high reliability, with a Cronbach's alpha of 0.857 for the general instrument, 0.825 for the domain Structure, and 0.809 for the domain Process. Conclusion: The instrument presented evidence of content validity and reliability for self-assessment, implementation and evaluation of the PSC in health institutions.